Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1088/1126-6708/2007/09/041
|View full text |Cite
|
Sign up to set email alerts
|

The phase structure of a chirally invariant lattice Higgs-Yukawa model for small and for large values of the Yukawa coupling constant

Abstract: We consider a chirally invariant lattice Higgs-Yukawa model based on the Neuberger overlap operator D (ov) . As a first step towards the eventual determination of Higgs mass bounds we study the phase diagram of the model analytically in the large N flimit. We present an expression for the effective potential at tree-level in the regime of small Yukawa and quartic coupling constants and determine the order of the phase transitions. In the case of strong Yukawa couplings the model effectively becomes an O(4)-sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 20 publications
6
75
0
Order By: Relevance
“…m > 0 and s > 0. It was found that such a ferrimagnetic phase should exist deeply inside the anti-ferromagnetic phase [25]. In figure 4 we provide evidence for the existence of this ferrimagnetic phase.…”
Section: Results For Small Values Of the Yukawa Coupling Constantmentioning
confidence: 73%
See 4 more Smart Citations
“…m > 0 and s > 0. It was found that such a ferrimagnetic phase should exist deeply inside the anti-ferromagnetic phase [25]. In figure 4 we provide evidence for the existence of this ferrimagnetic phase.…”
Section: Results For Small Values Of the Yukawa Coupling Constantmentioning
confidence: 73%
“…The anticipated structure of the phase diagram can be inferred from our large N f computation in ref. [25]. In that large N f approach the Higgs field and the coupling constants are scaled according to…”
Section: Results For Small Values Of the Yukawa Coupling Constantmentioning
confidence: 99%
See 3 more Smart Citations